Market Potential and Financial Feasibility Analysis of Milkfish Floss with Addition Ulin Banana Corm (Musa X Paradisiaca L. AAB) - Wulandari, Sekar Ayu; Mutmainah, Dini Nafisatul; Humaidi, Taufiq Rahman; Firmansyah, Akbar Maulana; Nadhifah, Fairuz (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
This study analyses the market potential and financial feasibility of milkfish floss enriched with ulin banana corm, addressing a gap in literature concerning the economic viability of such sustainable food innovations. While prior research confirms the technical suitability of banana corms in food products, their commercial potential remains underexplored. Utilizing a mixed-methods approach, this research gathered qualitative data through in-depth interviews with experts, and quantitative data via a consumer questionnaire (n=70). The findings reveal significant financial promise, with a calculated profit margin of 43.3%, a positive Net Present Value (NPV) of Rp 51 million, an 80.18% Internal Rate of Return (IRR), and a two-year Payback Period (PBP). Consumer analysis indicates strong appreciation for the product's health benefits, natural ingredients, and unique taste, with a high overall acceptability score (3.9/5). However, the primary challenge identified is consumer hesitation due to differences in taste and texture compared to traditional milkfish floss. The discussion concludes that despite this barrier, the product holds strong potential for success, particularly among health-conscious and environmentally aware consumers. To achieve wider market acceptance, the study recommends investing in more efficient processing technology and implementing targeted marketing strategies that emphasize the product's nutritional advantages and sustainability credentials